Rehabilitation in Israel - Martz, Erin (Disability Studies Quarterly, 2003)
This article briefly overviews the civilian and military rehabilitation systems in Israel, as described by two employees of those systems. Though Israeli systems provide comprehensive social services to individuals who were injured as civilians, Israeli rehabilitation practices appear to be more extensive for individuals who were injured while serving in the military.